2016
DOI: 10.1038/srep18725
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain energetics induces mitochondrial fission arrest in Alzheimer’s Disease

Abstract: Altered brain metabolism is associated with progression of Alzheimer’s Disease (AD). Mitochondria respond to bioenergetic changes by continuous fission and fusion. To account for three dimensional architecture of the brain tissue and organelles, we applied 3-dimensional electron microscopy (3D EM) reconstruction to visualize mitochondrial structure in the brain tissue from patients and mouse models of AD. We identified a previously unknown mitochondrial fission arrest phenotype that results in elongated interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
170
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 52 publications
17
170
2
Order By: Relevance
“…Unlike dissociated neuronal culture in which the morphology of mitochondria in the soma is used to confirm neuronal health prior to imaging, explant culture does not allow access to RGC cell bodies. To circumvent this issue, we used mitochondrial membrane potential as a marker of axonal health by labeling mitochondria with tetramethylrhodamine methyl ester (TMRM), a membrane potential dependent fluorescent dye (Trushina et al, 2012; Verburg and Hollenbeck, 2008; Zhang et al, 2016). We found that Armcx1 overexpression induced a significant increase of the motile mitochondria pool compared to the PLAP control (Figure 2A and 2B and Movie S1).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike dissociated neuronal culture in which the morphology of mitochondria in the soma is used to confirm neuronal health prior to imaging, explant culture does not allow access to RGC cell bodies. To circumvent this issue, we used mitochondrial membrane potential as a marker of axonal health by labeling mitochondria with tetramethylrhodamine methyl ester (TMRM), a membrane potential dependent fluorescent dye (Trushina et al, 2012; Verburg and Hollenbeck, 2008; Zhang et al, 2016). We found that Armcx1 overexpression induced a significant increase of the motile mitochondria pool compared to the PLAP control (Figure 2A and 2B and Movie S1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next determined the levels of Drp1 protein specifically in mitochondria, using a method reported in recent studies that evaluates Drp1 protein levels in the mitochondrial outer membrane by flow cytometry [28, 33]. In this assay, isolated mitochondria derived from NC and DM rats were first selected/gated according to light scattering properties (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as a major regulator of mitochondrial fission, Drp1 typically resides in an inactive form in the cytosol and on activation translocates to the mitochondria. In addition, experimental evidence suggests that phosphorylation of Drp1 at S616 is associated with mitochondrial elongation or fragmentation [33]. …”
Section: Resultsmentioning
confidence: 99%
“…We detected age-related morphogenetic abnormalities resulting in accumulation of mitochondria with intermingled thin (“pinched”) and enlarged segments, indicative of mitochondrial dysfunction. This phenotype has just been detected in AD brains, where it has been termed “mitochondria-on-a-string” (MOAS) (Zhang et al, 2016). Thus, the discovery of this phenotype in the aged rhesus monkey may help reveal the etiology of mitochondrial deficits in human AD.…”
Section: Introductionmentioning
confidence: 99%